Medial Epicondylitis: A Systematic Review on Causes, Symptoms and Treatment - Grzelak, Alicja (Quality in Sport, 2024)
Introduction: Medial epicondylitis, often called golfer's elbow, involves pain on the inner side of the elbow. It usually results from repetitive strain on the tendons that connect the forearm muscles to the medial epicondyle. While commonly linked to golfing, it can affect people engaged in various activities requiring repetitive wrist flexion and gripping. Purpose of work: This paper aims to provide a comprehensive overview of the pathogenesis, imaging characteristics, and treatment strategies for medial epicondylitis. State of knowledge: Medial epicondylitis can be worsened by activities that require forceful gripping, such as golfing or weightlifting [1][2]. The condition has been extensively studied and is well-documented in the scientific literature. Various treatments are available, including conservative methods like rest, physical therapy, and injections, as well as surgical interventions for persistent cases. Material and methods: This review draws upon an in-depth analysis of current scientific literature, including recent publications in prominent medical journals and relevant research studies. To identify pertinent scientific publications and research studies, comprehensive searches were conducted on widely recognized academic databases, such as PubMed and Google Scholar. Summary: Medial epicondylitis, also known as "golfer's elbow," is characterized by pain and tenderness over the bony prominence on the inner side of the elbow. It often results from repetitive strain or overuse of the muscles that flex the wrist and pronate the forearm [3]. Diagnostic imaging, such as X-rays and MRI, can help evaluate this condition [1][4]. Treatment typically involves a combination of conservative approaches, including rest, physical therapy, and anti-inflammatory medications, as well as more invasive options like corticosteroid injections or surgery for persistent cases.